Organisation and tyrosine hydroxylase and calretinin immunoreactivity in the main olfactory bulb of paca (cuniculus paca): a large caviomorph rodent - Castro Sasahara, Tais Harumi de [UNESP]; Leal, Leonardo Martins [UNESP]; Spillantini, Maria Grazia; Fernandes Machado, Marcia Rita [UNESP] (Springer, 2015)
The majority of neuroanatomical and chemical studies of the olfactory bulb have been performed in small rodents, such as rats and mice. Thus, this study aimed to describe the organisation and the chemical neuroanatomy of the main olfactory bulb (MOB) in paca, a large rodent belonging to the Hystricomorpha suborder and Caviomorpha infraorder. For this purpose, histological and immunohistochemical procedures were used to characterise the tyrosine hydroxylase (TH) and calretinin (CR) neuronal populations and their distribution. The paca MOB has eight layers: the olfactory nerve layer (ONL), the glomerular layer (GL), the external plexiform layer (EPL; subdivided into the inner and outer sublayers), the mitral cell layer (MCL), the internal plexiform layer (IPL), the granule cell layer (GCL), the periventricular layer and the ependymal layer. TH-ir neurons were found mostly in the GL, and moderate numbers of TH-ir neurons were scattered in the EPL. Numerous varicose fibres were distributed in the IPL and in the GCL. CR-ir neurons concentrated in the GL, around the base of the olfactory glomeruli. Most of the CR-ir neurons were located in the MCL, IPL and GCL. Some of the granule cells had an apical dendrite with a growth cone. The CR immunoreactivity was also observed in the ONL with olfactory nerves strongly immunostained. This study has shown that the MOB organisation in paca is consistent with the description in other mammals. The characterisation and distribution of the population of TH and CR in the MOB is not exclusively to this species. This large rodent shares common patterns to other caviomorph rodent, as guinea pig, and to the myomorph rodents, as mice, rats and hamsters.
Keywords: Calcium-binding protein; Dopamine; Immunohistochemistry; Neuroanatomy; Olfactory system; Rodent